Modeling shallow soil moisture dynamics in mountainous landslide active regions - Dai, Jia-Ying; Cheng, Su-Ting (Frontiers in Environmental Science, 2022)
Under the worsening climate change, the mountainous landslide active regions are more likely to suffer severe disasters threatening residents. To predict the occurrence of landslides, shallow soil moisture lying in the interface of the hydrological processes has been found as one of the critical factors. However, shallow soil moisture data are often scarce in the landslide active regions. To overcome the severe measurement deficiencies and provide predictions of soil moisture dynamics, we construct a physically-based shallow soil moisture model based on the assumptions of ideal flow, homogeneous and isotropic soil textures, and 1-dimensional water movement dominant by gravity forces. In the model, the meteorological conditions and the physical soil properties are taken into consideration. With limited field measurements, the model can provide reasonably accurate soil moisture predictions. In recognition of the seasonal weather characteristics, we perform a series of sensitivity analyses to examine the response of shallow soil moisture and relate the hydrological processes to air temperature, precipitation intensity, duration, and combinations thereof. Complex interactions of hydrological processes are found with variations in precipitation and air temperature, depending on the interlinked boundary conditions of the soil and water. It demonstrates a strong need for a decent forecast of the complex shallow soil moisture dynamics and the associated hydrologic processes in mountain regions to cope with climate change for landslide preparation and agricultural adaptation in the future.